Improved reconstruction of highly boosted $$τ $$ τ -lepton pairs in the $$τ τ → (μ ν _{μ }ν _{τ })(\text {hadrons}+ν _{τ })$$ τ τ → ( μ ν μ ν τ ) ( hadrons + ν τ ) decay channels with the ATLAS detector - ATLAS Collaboration (European Physical Journal C: Particles and Fields, 2025)
Abstract This paper presents a new $$τ $$ τ -lepton reconstruction and identification procedure at the ATLAS detector at the Large Hadron Collider, which leads to significantly improved performance in the case of physics processes where a highly boosted pair of $$τ $$ τ -leptons is produced and one $$τ $$ τ -lepton decays into a muon and two neutrinos ( $$τ _μ $$ τ μ ), and the other decays into hadrons and one neutrino ( $$τ _had$$ τ had ). By removing the muon information from the signals used for reconstruction and identification of the $$τ _had$$ τ had candidate in the boosted pair, the efficiency is raised to the level expected for an isolated $$τ _had$$ τ had . The new procedure is validated by selecting a sample of highly boosted $$Z→ τ _μ τ _had$$ Z → τ μ τ had candidates from the data sample of 140 $$fb^{-1}$$ fb - 1 of proton–proton collisions at 13 TeV recorded with the ATLAS detector. Good agreement is found between data and simulation predictions in both the $$Z→ τ _μ τ _had$$ Z → τ μ τ had signal region and in a background validation region. The results presented in this paper demonstrate the effectiveness of the $$τ _had$$ τ had reconstruction with muon removal in enhancing the signal sensitivity of the boosted $$τ _μ τ _had$$ τ μ τ had channel at the ATLAS detector.